Pemanfaatan Kotoran Ternak Sebagai Pupuk Kompos Ramah Lingkungan Di Kelurahan Batu Bersurat - Chicka Willy Yanti; Putri Rahmadani; Ledy Yuhana; Zuhruf Salsabilla; Muhammad Syahrul Mukminin; Ardiyansyah Ardiyansyah; Muhammad Raihan Al- baqi; Nurul Fadhilah; Diva Sayyidina Rabbani; Fitri Amatillah; Widya Ningsih Atya Ningrum (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The purpose of this activity is so that the environment of Batu Bersurat Village, XIII Koto Kampar District, Kampar Regency can become a clean and uncontaminated environment from cow dung. Cow dung can be processed into compost. Compost is an organic fertilizer made from animal waste that has undergone a fermentation process. The advantage of this compost is that it is environmentally friendly, can increase the income of farmers, and can increase soil fertility by repairing physical damage to the soil due to excessive use of inorganic (chemical) fertilizers. Batu Bersurat Village is an area with potential in agriculture, plantation and animal husbandry. The existence of cattle owned by the community has the potential to be used as compost which can be used for agriculture as well as for the fertility of plantation crops. However, the lack of knowledge of residents about the methods and benefits of making compost from cow manure causes cow manure to be thrown away, therefore people still use chemical fertilizers as a medium for the fertility of their plants. Therefore, a practice was held to make use of compost from cow manure in Batu Bersurat Village, District XIII Koto Kampar, Kampar Regency.